Vulamasango Singene: sociological analysis of a rural social movement - Kirchmann, Gail Lynne (Rhodes University, Faculty of Humanities, Department of Sociology)
This dissertation tests the claim made by a large membership-based organisation that it is a social movement. The organisation, Vulamasango Singene (VS) operates across the rural areas of large parts of the Eastern Cape Province. It has, for twenty years, advocated for the re-opening of land restitution claims for a specific category of forced removal known as "betterment" . This study provides an analysis of an organisation that has yet to achieve its objective in spite of sufficient financial resources, logistical and strategic support, numeric strength and the legal clarity of its demand. The research is situated within the framework of social movement theory. The study examined the origins, institutional infrastructure, demographic make-up, activities and culture of VS. These were analysed against four components that are identified in the literature as key characteristics of a social movement. These are: (i) informal networks (as opposed to structured and managed engagements); (ii) a plurality of actors (as opposed to a homogenous grouping); (iii) mobilising around issues of conflict; and (iv) sharing common beliefs and demonstrating solidarity. Data were gathered through an archival study and field research. Semi-structured interviews were carried out with a sample of VS's leadership, and staff of the non-governmental organisation in which VS originated, as well as expert informants in the land reform arena. The findings with respect to each of the criteria were: (i) VS's structure was rigid and internal communication was largely formal. (ii) There was almost no demographic or political diversity within VS. (iii) VS had, in the past, mobilised around issues of conflict, but there had been no mobilisation for ten years. (iv) While there was some evidence of sharing common beliefs and demonstrating solidarity, this was limited. The conclusion reached was that VS is not a social movement. This does not imply that VS is not an important democratic or representative organisation. It does, however, provide a theoretical position from which VS, and other organisations, can direct further action. The study touched on the relationship between northern donors, local professional NGOs and grassroots organisations in South Africa. Interactions among these institutions impact on the way that organisations and social movements develop. Comparisons with other similar organisations were made and similarities and differences were highlighted. It was suggested that, because of the importance of the issue, further research in this regard is necessary.
Keywords: Social movements -- South Africa -- Eastern Cape; Land reform -- South Africa; Non-governmental organizations -- South Africa; Reparations for historical injustices -- South Africa; Betterments -- South Africa